Risk scores for community acquired pneumonia in elderly and geriatric patients Risiko-Scores zur ambulant erworbenen Pneumonie bei älteren und geriatrischen Patienten - Pflug, M. A.; Wesemann, T.; Thiem, U.; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2015)
Background: Community-acquired pneumonia (CAP) is still an important and serious disease for elderly and geriatric patients. Aims: For epidemiological and clinical reasons it is important to collate the frequencies of the various degrees of severity of CAP and to obtain information on the spread and degree of the threat to the various risk groups by CAP. In outpatient treatment a simple to execute prognosis score can be used to objectify the assessment of the clinical status of a patient and to support therapeutic decision-making. For this purpose knowledge of the appropriate instruments should be available to potential users. Material and methods: Since the 1990s a variety of risk scores for stratification of CAP have been developed and evaluated. This article presents the content and value of the available risk scores whereby the advantages and disadvantages of the individual scores are critically compared. Special emphasis is placed on the importance of the risk scores for geriatric patients. Results: At present the decision about outpatient or inpatient treatment is primarily based on the risk score CRB-65. Criteria for intensive care unit admissions are provided by the modified American Thoracic Society (ATS) set of criteria. Overall, risk scores are less reliable for elderly patients than for younger adults. Conclusion: For treatment decisions for the elderly, functional aspects should also be considered in addition to the aspects of risk scores discussed here. In particular, the decision about inpatient admission for elderly, geriatric CAP patients should be made on an individual basis taking the benefit-risk relationship into consideration.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Hospitalization; Prognosis; Recommendations; Risk assessment; Severity of illness index